1997
DOI: 10.1016/s0092-8674(00)81856-5
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Rigidity Causes Strengthening of Integrin–Cytoskeleton Linkages

Abstract: To move forward, migrating cells must generate traction forces through surface receptors bound to extracellular matrix molecules coupled to a rigid structure. We investigated whether cells sample and respond to the rigidity of the anchoring matrix. Movement of beads coated with fibronectin or an anti-integrin antibody was restrained with an optical trap on fibroblasts to mimic extracellular attachment sites of different resistance. Cells precisely sense the restraining force on fibronectin beads and respond by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
950
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,159 publications
(1,022 citation statements)
references
References 47 publications
58
950
1
3
Order By: Relevance
“…It has been shown that forces exerted on focal adhesions stretch the receptor-ligand bonds and aid the growth of adhesions (15). The softer ECMs undergo larger deformation and thus lead to greater distances between receptors and ligands, which in turn is thought to impair adhesion bond formation (16).…”
Section: Cell-ecm Adhesion Dynamicsmentioning
confidence: 99%
“…It has been shown that forces exerted on focal adhesions stretch the receptor-ligand bonds and aid the growth of adhesions (15). The softer ECMs undergo larger deformation and thus lead to greater distances between receptors and ligands, which in turn is thought to impair adhesion bond formation (16).…”
Section: Cell-ecm Adhesion Dynamicsmentioning
confidence: 99%
“…87 Integrins are mechanoreceptors, able to sense substrate rigidity via periodic contraction of the integrinassociated cytoskeleton. 88 This results in the recruitment of additional cytoskeletal elements to strengthen the interaction, 89 which themselves are sensitive to the presence of mechanical force. 90 Lack of tensional forces may compromise the ability of integrins to mediate productive signaling into the cell, particularly among signaling events that are dependent upon the cytoskeleton.…”
Section: Signaling Cascades and The Integrin Rheostatmentioning
confidence: 99%
“…Various micromechanical techniques have been established during the last few years to measure local elastic moduli or the stress-strain relationship of whole cells including micropipette aspiration techniques [12][13][14], atomic force microscopy [15], optical tweezers [16,17], or cell poking with glass rods [18]. Based on these techniques, the elastic properties of cell envelopes, whole nucleated cells and erythrocytes have been extensively studied [1,19].…”
Section: Introductionmentioning
confidence: 99%